Elisabetta Sirani - Modesti, Adelina (Illuminating Women Artists, 2023)
Elisabetta Sirani of Bologna (1638-1665) was one of the most innovative and prolific artists of the Bolognese School. Not only a painter, she was also a printmaker and a teacher. Based on extensive archival documentation and primary sources ? including inventories, sale catalogues and her work diary ? Elisabetta Sirani provides an overview of the life, work, critical fortune and legacy of this successful Baroque artist. Placing her within the context of the post-Tridentine society that both inhibited and supported her, Modesti examines Sirani's influence on many of the artists studying at Bologna's school for professional women artists, as well as her significance in the professionalisation of women?s artistic practice in the seventeenth century.00Beautifully illustrated throughout, Elisabetta Sirani focuses on women?s agency. More specifically, it explores Sirani?s identity as both a woman and an artist, including her professional ambition, self-fashioning and literary construction as Bologna?s pre-eminent cultural heroine